Germaphobia! Does Our Relationship With and Knowledge of Biodiversity Affect Our Attitudes Toward Microbes? - Robinson, Jake M.; Cameron, Ross; Jorgensen, Anna (Frontiers in Psychology, 2021)
Germaphobia –– a pathological aversion to microorganisms –– could be contributing to an explosion in human immune-related disorders via mass sterilisation of surfaces and reduced exposure to biodiversity. Loss of biodiversity and people’s weaker connection to nature, along with poor microbial literacy may be augmenting the negative consequences of germaphobia on ecosystem health. In this study, we created an online questionnaire to acquire data on attitudes towards, and knowledge of microbes. We collected data on nature connectedness and interactions with nature and explored the relationships between these variables. Although the study had an international reach (n = 1,184), the majority of responses came from England, UK (n = 993). We found a significant association between attitudes towards microbes and both duration and frequency of visits to natural environments. A higher frequency of visits to nature per week, and a longer duration spent in nature per visit, were significantly associated with positive attitudes towards microbes. We found no association between nature connectedness and attitudes towards microbes. We found a significant relationship between knowledge of ‘lesser known’ microbial groups (e.g., identifying that fungi, algae, protozoa, and archaea are microbes) and positive attitudes towards microbes. However, we also found that people who correctly identified viruses as being microbes expressed less positive views of microbes overall –– this could potentially be attributed to a ‘COVID-19 effect’. Our results suggest that basic microbial literacy and nature engagement may be important in reducing/preventing germaphobia-associated attitudes. The results also suggest that a virus-centric phenomenon (e.g., COVID-19) could increase broader germaphobia-associated attitudes. As the rise of immune-related disorders and mental health conditions have been linked to germaphobia, reduced biodiversity, and non-targeted sterilisation, our findings point to a feasible strategy to potentially help ameliorate these negative consequences. Further research is needed, but greater emphasis on microbial literacy and promoting time spent in nature could potentially be useful in promoting resilience in human health and more positive/constructive attitudes towards the foundations of our ecosystems – the microorganisms.